# How do you solve #-38= 2( x - 4) - 7x#?

##### 2 Answers

#### Answer:

x=6

#### Explanation:

First, to get rid of the parentheses, you would distribute the 2. Then you would get -38 = 2x - 8 - 7x. By combining like terms, you would simplify that to -38 = -8 -5x. To get the term with a variable on one side, you would add 8 to both sides, leaving you with -30 = -5x. Dividing by -5 on both sides would leave you with x=6.

#### Answer:

#### Explanation:

#"distribute bracket on right side"#

#-38=2x-8-7x#

#rArr-38=-5x-8#

#"add 8 to both sides"#

#-38+8=-5xcancel(-8)cancel(+8)#

#rArr-5x=-30larrcolor(blue)"reverse equation"#

#"divide both sides by "-5#

#(cancel(-5) x)/cancel(-5)=(-30)/(-5)#

#rArrx=6#

#color(blue)"As a check"# Substitute this value into the right side of the equation and if equal to the left side then it is the solution.

#"right "=2(6-4)-(7xx6)=4-42=-38=" left"#

#rArrx=6" is the solution"#